Analysis of Secondary Physical Education Teacher Recruitment Examination: Focused on Sport Biomechanics Questions from 2016 through 2022 - Jeehoon Sohn; Jonghyun Yang (Korea Institute of Sport Science, 2022)
PURPOSE This study aimed to analyze the sport biomechanics questions in the 'Secondary Physical Education Teacher Recruitment 1st Exams' and find the orientation for future exams. METHODS Twenty-one sports biomechanics questions (49 detailed questions) in the last 7 years (2016-2022) were classified into four types (evaluation content factors, classification of educational goal, sports application or not, classroom connection, and including calculation) and analyzed. RESULTS The recruitment exams had the following characteristics. First, only approximately 22.4% of the questions were related to the secondary physical educational field. Second, only 34% were sports-applied questions. In addition, according to Bloom's classification of educational evaluation, 36.7% of knowledge-level questions, 40.8% comprehension-level questions, and 22.4% application-level questions were accounted for. Finally, the questions tended to be considerably biased towards specific items (kinetics and kinematics understanding and application of linear and angular motion). CONCLUSIONS Sport biomechanics questions in the 'Secondary Physical Education Teacher Recruitment 1st Exams' should be based on questions that are likely to occur in the field of secondary physical education, to occur in real sports situations, and to be asked by students. Additionally, rather than asking for simple knowledge or comprehension, the proportion of questions in the application level should be increased.